2017
DOI: 10.1177/0265407517699713
|View full text |Cite|
|
Sign up to set email alerts
|

The buffering effect of peer support on the links between family rejection and psychosocial adjustment in LGB emerging adults

Abstract: Lesbian, gay, and bisexual (LGB) emerging adults often seek support from their peers if they lack support from their family of origin. We predicted that peer social support would moderate the link between negative family relationships and psychosocial adjustment, such that in the context of family rejection, experiencing more peer support would predict lower levels of anxiety, depression, and internalized homonegativity (IH) and higher self-esteem. Sixty-two (27 females) LGB individuals (ages 17–27, M = 21.34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 75 publications
(110 reference statements)
1
62
1
Order By: Relevance
“…Additional interpersonal-level factors. In addition to supportive adults in schools, the working group identified peers in schools as sources of social support for LGBTQ students, 23,43,44 and some early work points to the potential role of parents in schools to champion the inclusion of LGBTQ students within school programs and policies. 45,46 Table 1 offers a summary of these factors with research and programmatic questions of interest for each factor identified by the working group.…”
Section: Supportive Adults In Schoolsmentioning
confidence: 99%
“…Additional interpersonal-level factors. In addition to supportive adults in schools, the working group identified peers in schools as sources of social support for LGBTQ students, 23,43,44 and some early work points to the potential role of parents in schools to champion the inclusion of LGBTQ students within school programs and policies. 45,46 Table 1 offers a summary of these factors with research and programmatic questions of interest for each factor identified by the working group.…”
Section: Supportive Adults In Schoolsmentioning
confidence: 99%
“…Adequate social support will offset or moderate the negative impact of minority stress on mental health. For example, social support has been found to serve as a buffer against the negative effects of minority stress and depressive symptoms among sexual minorities [20,21]. However, sexual minority individuals are more likely to suffer low levels of social support [22], which results in impaired mental health.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we hypothesize that the level of social support from family will be lower than the social support from friends and from significant other among Chinese sexual minority men; we expect that, these differences will not be found in heterosexual men. Next, given the large body of evidence suggesting that social support is associated with mental health [17][18][19][20][21][22][23][24], we hypothesize that social support will be inversely associated with depressive symptoms in Chinese men. Finally, based on previous research, social support could serve as a moderator and a mediator in the relationship between sexual minority identity and mental health [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This body of research has documented that sexual minority youth who receive greater levels of family/parental support, [15][16][17][18][19] friend/peer support, 18,19 community support, 18 and/or school support 19,20 report better personal outcomes than sexual minority youth who receive less support. This applies to outcomes such as psychological distress and depressive symptoms, [15][16][17]19,20 self-esteem, [17][18][19] suicidality, 17 and risk behaviors. 17 Furthermore, some support types (e.g., peer support) compensate for the absence of others (e.g., family support), buffering lesbian, gay, and bisexual (LGB) youth against suboptimal health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…17 Furthermore, some support types (e.g., peer support) compensate for the absence of others (e.g., family support), buffering lesbian, gay, and bisexual (LGB) youth against suboptimal health outcomes. 16 It is nevertheless unclear whether or not these associations differ between sexual minority and gender minority/transgender youth, as studies have either aggregated the two groups 15,17,18,20 or focused exclusively on LGB youth. 16,19 Studies examining the role of social relationships in mediating the associations between adolescent sexual orientation and health-that is, health disparities between sexual minority and heterosexual youth-are scarcer.…”
Section: Introductionmentioning
confidence: 99%